Review Paper on Black Money in India & its Effect - Pandey, Mr. Kunthlesh Kumar (IJRDO - Journal of Applied Management Science, 2016)
Black money is not only the problem ofIndian economy, but it also transcends theborders and has become a global dilemma.Recently, various studies have taken placeunder the Government of India to tackle theproblem of black money in India. Thosestudies have revealed some astonishing factsabout the black money market in India. Inthe last decade alone, India has lostapproximately $125 billion in illegal money.A study has revealed that the black moneyeven exceeds 10% of our Gross DomesticProduct. This paper represents theframework, policy options and strategiesthat Indian Govt. should adopt to tackle withthis issue and also describes the futurechallenges to be faced by Govt. in thiscontext. It also studies the one of the mainreason behind the generation of black moneyi.e. corruption. It shows up to what extent,the corruption leads to its generation whichhas considerable impact on various sectionsof the society. At last but not least,conclusion of this paper isprovidedrepresenting the ongoing issue of blackmoney in our country and its futurecourse ofaction. Hopefully, this would contribute toan informed approach on thisissue as wemove forward in this context